Fine structure of the lungs of great gerbils which are infected with mycobacterium tuberculosis Mt.avium (Experimental biology, 2016)
Cases of bovine tuberculosis and human species in domestic, wild and zoo animals were registered in many countries around the world. A significant impact on the occurrence, and during the infectious process provides a degree of virulence, the dose and the penetration of mycobacterium tuberculosis, as well as the level of resistance of animals. It is known that in the infected organism develops paraspecific reaction, nonspecific in its structure, due to mycobacterium tuberculosis etiology and specific inflammation typical of tuberculosis, which is the essence of the two main phases of tissue reactions immunity. A study of the fine structure of the lungs of great gerbils which are infected with mycobacterium tuberculosis Mt.avium was found in the lungs pronounced pathological process leading education tuberculosis primary tubercles, also observed the progression up to necrosis and rub in some parts of the body characteristic structure.
Keywords: hypoxia; respiratory section; epithelium; endothelium; surfactant; giperemiya; makpofag; nekroz.